Examining the relationship between yoga practice and body image satisfaction among female adults with social media exposure - Quarte, Patricia L.
This study examined the relationship between yoga practice and body image satisfaction among female adults, predominantly those with social media exposure, The research objectives are: 1) To check if the body dissatisfaction and drive for thinness standardized test results relate to their yoga practice and 2) To examine how the body dissatisfaction and drive for thinness standardized test results relate to the time they spend using social media. A four-part survey questionnaire was disseminated online that garnered a total of 81 respondents, with a mean age of 33.54 and 8.41 SD. 45 respondents or 55.56% practices Ashtanga, and 28 respondents or 34.57% said that they practice yoga more than thrice a week. This study did not delve into how long the respondents have been practicing yoga, as in starting from the beginning of when they decided to do yoga. Through the R Project for Statistical Computing, findings have shown that there is a demonstrated weak relationship between yoga practice and body image satisfaction. It was determined that body image satisfaction in terms of body dissatisfaction has shown no correlation with yoga practice in terms of all its categories (style, frequency, duration, and location of practice). While body image satisfaction in terms of drive for thinness has shown a correlation with yoga practice, specifically with style, frequency, and location. Interestingly, frequency and duration are inversely correlated with the drive for thinness. The results of this correlational study suggested its relevance to issues surrounding body image through yoga. Primarily, it implies that when the frequency and duration of yoga practice increase, an individual’s drive for thinness will decrease and go the other way around.